Beyond the reactionary sea change: Antimodern thought, American politics and political science - Magalhães, Pedro T. (Frontiers in Political Science, 2022)
This article examines the migration of reactionary antimodern thought from Europe to the United States of America. It assesses the impact that the work of two antimodern thinkers, Leo Strauss and Eric Voegelin, had on two distinct domains of American thought, namely, conservative political ideology and academic political science. The paper argues that the antimodern perspective, eagerly absorbed by many intellectuals, has pushed American conservatism not only in an anti-liberal, but also in an antidemocratic direction. On the other hand, in academic political science, Strauss's and Voegelin's critiques of modernity, though certainly audible and noted, were neither taken seriously nor confronted in depth by the mainstream of the discipline. This neglect should be corrected, I contend, for contemporary political science is in need of a mature and nuanced theory of modernity that is capable of rising up to the radical challenge of the antimoderns.